Advancing Stage 2 Research on Measures for Monitoring Kindergarten Reading Progress. (January 2018) - Clemens, Nathan H.; Soohoo, Michelle M.; Wiley, Colby P.; Hsiao, Yu-Yu; Estrella, Ivonne; Allee-Smith, Paula J.; Yoon, Myeongsun
Although several measures exist for frequently monitoring early reading progress, little research has specifically investigated their technical properties when administered on a frequent basis with kindergarten students. In this study, kindergarten students ( N = 137) of whom the majority was receiving supplemental intervention for reading skills were monitored using Letter Sound Fluency, Phoneme Segmentation Fluency, Word Reading Fluency, Nonsense Word Fluency, Highly Decodable Passages, and Spelling on a biweekly basis between February and May. Acceptable reliability was observed for all measures. Analyses of slope validity using latent growth models, latent change score models, and slope differences according to level of year-end achievement indicated that the relation of slope to overall reading skills varied across the measures. A suggested approach to kindergarten students' reading progress is offered that includes Letter Sound Fluency and a measure of word-reading skills to provide a comprehensive picture of student growth toward important year-end reading outcomes.